Shifts in the seasonal trophic ecology of larvae and juveniles of European hake ( Merluccius merluccius ): From the Galician upwelling system (NW Spain) - Raúl Laiz‐Carrión; Águeda Cabrero; José María Quintanilla; Alma Hernández; Amaya Uriarte; Jesús Gago; José María Rodríguez; Carmen Piñeiro; Alberto García; Fran Saborido‐Rey (Fisheries Oceanography, 2022)
The trophic ecology of European hake ( Merluccius merluccius ) larvae and early‐juveniles from the Iberian shelf off Galicia (NW Spain) are assessed by means of stable isotopes (SIA) and nutritional condition in conjunction with hydrobiological variations observed during the winter and summer season of 2012. Hake early‐juveniles (18–47 mm SL) showed higher δ 15 N than larvae (3–11 mm SL) together with the microzooplankton (55–200 μm) and mesozooplankton (>200 μm) during both seasons. Low δ 15 N values and high variability in both zooplankton and hake larvae were found during winter coinciding with an unusually strong upwelling event. Inversely, high δ 15 N content in zooplankton in summer suggests strong nitrogen reutilization. However, hake larvae sampled in summer had a higher RNA:DNA ratio in line with higher Fulton condition factors than those sampled in winter. Higher δ 13 C values for microzooplankton and mesozooplankton and hake larvae in summer compared to late winter point to prey availability differences. The relationship between nitrogen and carbon stable isotopes versus size or weight suggests an ontogenetic shift in the diet of hake larvae. Early‐juveniles had a lower isotopic niche width compared to larvae in both late winter and summer, indicating a trophic specialization related to changes following settlement process from planktonic life to demersal habitat. Higher trophic specialization was observed in summer, which recorded a narrower isotopic niche and higher trophic position estimations.